Electroconvulsive therapy in perspective, or a critique of electroshock - Magalhães, Vinicius Pinheiro de; Barros, Larissa Daiane Vieira (Argumentum, 2023)
This essay sets out the guiding principles of Electroconvulsive Therapy (ECT), a psychiatric medical procedure that consists of inducing seizures by administering electrical currents to the brain for therapeutic purposes. The purpose of the text is to weave an onto-epistemological critique of ECT and its theoretical-conceptual foundations in light of Psychiatric Reform and the Social Determination of Mental Health. It is a theoretical essay based on an extended literature review. We understand ECT to be a technique based on a narrow theoretical trend that is applied its users in the name of invasive intervention oriented to short- to medium-term action, the purpose of which is to control the bodies of historically vulnerable segments of society.